EFFECT OF POST-TRANSITION DYNAMICS ON EMPLOYEES’ JOB PERFORMANCE: THE BANGSAMORO REGION PERSPECTIVE - Madid, Nabilah U. H.; Daud, Yammie Palao (DIA: Jurnal Administrasi Publik, 2024)
This study evaluates the job performance of government employees during the transition period from the Autonomous Region in Muslim Mindanao (ARMM) to the Bangsamoro Autonomous in Muslim Mindanao (BARMM). It specifically attempts to determine the employees' job performance regarding efficiency, timeliness, and responsiveness. This study used a descriptive quantitative method to analyze the data gathered. It also employed a qualitative approach in analyzing and interpreting the data. A convenient sampling method was employed in the data gathering. Key informants' interview was also employed to extract raw data from the participants. Essential statistical tools like mean and standard deviation were also resorted to in the data treatment. The study results revealed that the employees performed well on the three variables. However, timeliness was found to have the lowest mean among the variables. The finding implies that statement indicators under this variable could have been performed better by the employees during the transition period.